2022
DOI: 10.3389/fonc.2022.816638
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Model for Preoperative Differentiation of Glioblastoma, Brain Metastasis and Primary Central Nervous System Lymphoma: A Pilot Study

Abstract: BackgroundNeuroimaging differentiation of glioblastoma, primary central nervous system lymphoma (PCNSL) and solitary brain metastasis (BM) remains challenging in specific cases showing similar appearances or atypical features. Overall, advanced MRI protocols have high diagnostic reliability, but their limited worldwide availability, coupled with the overlapping of specific neuroimaging features among tumor subgroups, represent significant drawbacks and entail disparities in the planning and management of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…Normal vs. LGG vs. HGG Custom CNN model 5-fold CV 95 2. MEN vs. Glioma vs. PT Custom CNN model 5-fold CV 94.74 Guo et al [ 128 ] 2022 GBM vs. AST vs. OLI Custom CNN 3-fold CV SEN = 0.772, SPE = 93.0%, AUC = 0.902 87.8% Rizwan et al [ 130 ] 2022 Grade I vs. Grade II vs. Grade III Custom CNN No info shared 97.14% Tariciotti et al [ 123 ] 2022 Metastasis vs. GBM vs. PCNSL Resnet101 Hold-out PRE = 91.88%, SEN = 90.84%, SPE = 96.34%, F1 score = 91.0%, AUC = 0.92 94.72% 4 classes Ahammed et al [ 72 ] 2019 Grade I vs. Grade II vs. Grade III vs. Grade IV VGG19 No info shared PRE = 94.71%, SEN = 92.72%, SPE = 98.13%, F1 score = 93.71% 98.25 Mohammed et al [ 51 ] 2020 …”
Section: Resultsmentioning
confidence: 99%
“…Normal vs. LGG vs. HGG Custom CNN model 5-fold CV 95 2. MEN vs. Glioma vs. PT Custom CNN model 5-fold CV 94.74 Guo et al [ 128 ] 2022 GBM vs. AST vs. OLI Custom CNN 3-fold CV SEN = 0.772, SPE = 93.0%, AUC = 0.902 87.8% Rizwan et al [ 130 ] 2022 Grade I vs. Grade II vs. Grade III Custom CNN No info shared 97.14% Tariciotti et al [ 123 ] 2022 Metastasis vs. GBM vs. PCNSL Resnet101 Hold-out PRE = 91.88%, SEN = 90.84%, SPE = 96.34%, F1 score = 91.0%, AUC = 0.92 94.72% 4 classes Ahammed et al [ 72 ] 2019 Grade I vs. Grade II vs. Grade III vs. Grade IV VGG19 No info shared PRE = 94.71%, SEN = 92.72%, SPE = 98.13%, F1 score = 93.71% 98.25 Mohammed et al [ 51 ] 2020 …”
Section: Resultsmentioning
confidence: 99%
“…Although multiparametric MRI represents the current imaging gold standard in primary and metastatic brain neoplasms, PET studies have the unique and complementary ability to evaluate and characterize the metabolic patterns within the tumor and non-tumor tissues through the use of selected radiolabeled tracers [ 84 , 85 , 86 ]. The roles of different PET tracers in tumor diagnosis and post-treatment response assessment have been largely discussed and validated by international consensuses and recommendations [ 87 , 88 , 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis of 10 articles by You et al suggested that arterial spin labeling could differentiate between PCNSL and HGG with an AUC of 0.86 ( 27 ). Additionally, a diagnostic model constructed with a deep learning algorithm based on MR imaging was used to differentiate PCNSLs, glioblastoma and brain metastases, with an AUC of 0.98 in the differential diagnosis of PCNSL ( 28 ). However, PET-CT still has great diagnostic advantages over other techniques in terms of imaging detection methods that rely on a single index.…”
Section: Discussionmentioning
confidence: 99%